Penafsiran Ayat-Ayat Thaharah - Nabila Putri Amelia; Siska Heriani; Alya Junaidi; Hanifa Sayadatin Nadira; Edi Hermanto (CV. ITTC INDONESIA, 2026)
Purification is an essential requirement for performing worship, particularly prayer, which holds a significant place in Islamic teachings. However, understanding of purification is often limited to the technical aspects of Islamic jurisprudence, without a deeper understanding of its meaning and purpose as stipulated in the Qur'an. Therefore, an interpretive study of the purification verses is crucial for a comprehensive understanding of the concept of purification. This study aims to analyze the interpretation of the purification verses in the Qur'an, specifically Surah al-Maidah verse 6 and Surah an-Nisa' verse 43, and to uncover the legal content and wisdom contained therein. This study uses a qualitative approach with library research. Data were obtained through a review of the Qur'an, the tafsir books of classical commentators, and relevant supporting literature. The research results show that the verses of thaharah emphasize the obligation to purify oneself before prayer through ablution and ghusl (ritual cleansing), and provide relief in the form of tayammum (purification) under certain conditions. These provisions reflect the balance between the demands of purity and the principle of convenience in Islamic law, while also demonstrating that thaharah serves not only as an outward purification but also as a spiritual preparation for performing worship.